Perfomance of the Gegesik Style Cirebon Mask Kalana Dance in the Context of Coastal Culture as a Source of Local Wisdom - Triana Pramadanti; Malarsih Malarsih; Hartono Hartono (Gondang: Jurnal Seni dan Budaya, 2023)
Gegesik-style Klana mask dance is one of the styles that have survived to the present day. The importance of maintaining and preserving the Gegesik-style Klana mask dance, which is comprised of dance elements presented in the form of a dance perfomance, is understood by a few people who have studied its dance elements. By comprehending the elements contained therein, the Gegesik style of the masked Klana dance will maintain its authenticity without altering a single aspect of the Gegesik style masked Klana dance's standard. Gegesik-style Klana mask dance has excellent appeal for ceremonial events, welcoming guests, and filling in events organized by government and non-government organizations. This study used qualitative research and an ethnochoreological methodology as a scalpel to investigate the textual components of dance. The Gegesik style Klana mask dance has eight text components: movement, dancers, make-up, clothing, floor patterns, music, property, and place of performance. Collecting data was done with observation, interviews, and document analysis. After conducting research, the researcher discovered that the form of perfomance of the Gegesik-style masked Klana dance consists of eight interrelated components that cannot be changed without altering its authenticity. Consequently, the Gegesik-style Cirebon masked Klana dance contains elements that cannot be easily altered, as well as meanings and values implicit in every movement, music, costume, and another component. Keywords: Gegesik Style Klana Mask Dance, Dance Perfomance, Ethnochoreology.